2002
DOI: 10.1001/archinte.162.15.1761
|View full text |Cite
|
Sign up to set email alerts
|

Patient Factors and Medication Guideline Adherence Among Older Women With Asthma

Abstract: Asthma is undertreated among older women, even those who are health care professionals. Women with advanced age and severe asthma were particularly at risk. Given that the greatest increase in asthma mortality has occurred among older women, further research is needed to examine physician prescribing patterns and patient beliefs in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 24 publications
4
81
1
1
Order By: Relevance
“…The NHS is a questionnaire-based longitudinal cohort study reporting incident physiciandiagnosed asthma. Several validation studies have been conducted in the original NHS, [16][17][18][19][20] suggesting that the questionnaire identifies a reasonable phenotype to investigate in asthma epidemiology. Unrecognized differences in exposures or treatment that affect diagnosis, or diagnostic methods themselves, may help explain the inconsistent results between the cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NHS is a questionnaire-based longitudinal cohort study reporting incident physiciandiagnosed asthma. Several validation studies have been conducted in the original NHS, [16][17][18][19][20] suggesting that the questionnaire identifies a reasonable phenotype to investigate in asthma epidemiology. Unrecognized differences in exposures or treatment that affect diagnosis, or diagnostic methods themselves, may help explain the inconsistent results between the cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Several validation studies have been conducted in the original NHS. [16][17][18][19][20] Case subjects were randomly selected from these confirmed cases among lifelong nonsmokers. Age-matched control subjects were selected from lifelong nonsmokers in the overall cohort who did not report asthma or asthma medication use in the preceding year.…”
Section: Demographics Of Case-control Populationmentioning
confidence: 99%
“…[14][15][16] Psychosocial factors related to noncompliance are well-recognized problems, and have been documented in literature with mixed results. Studies have suggested that age, 17,18 sex, 18 lower socioeconomic status, severity of disease, 17 drug choice, 7,19,20 number of medications prescribed, 18,19 drug tolerability, 7,20 regimen complexity, 18,20 co-morbid medical conditions, 17,19 family support, 21 self-efficacy, intention to comply, 22 physician-patient relationship, 23 satisfaction with health care 24 and depression 25,26 are associated with compliance. However, some of these studies are limited by specific race, 17,24 usage of nonvalidated tools, 22 and failure to exclude newly diagnosed patients and patients with co-existing medical illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Poor knowledge and drug adherence would be extent to which a patient's behavior coincides with health related advice and ability of the ic appointments as per scheduled, take medicines as prescribed, and life style modification are recommendation for prevention and In recent document, the world health organization recognized s a major problem in prevention and management of chronic disease including asthma and concluded that improving compliance would have more beneficial impact on health outcome that improving specific treatment for asthma. It is an acceptable fact for t medication that despite tremendous advances in diagnosis accuracy, if patients fail to recommended medication that expenses and efforts involved are virtually wasted [11][12][13][14][15]. In recent years various approaches have been made to utilize the industrial asthmagens in pre clinical and clinical studies .…”
Section: Introductionmentioning
confidence: 99%